Excessive Lending, Leverage, and Risk-Taking in the Presence of Bailout Expectations - Georgiou, Andreas (IMF Working Papers; Working Paper ;, 2009)
The financial crisis that began in 2007 has brought to the fore the issues of excesses in lending, leverage, and risk-taking as some of the fundamental causes of this crisis. At the same time, in dealing with the financial crisis there have been large scale interventions by governments, often referred to as bailouts of the lenders. This paper presents a framework where rational economic agents engage in ex ante excessive lending, borrowing, and risk-taking if creditors assign a positive probability to being bailed out. The paper also offers some thoughts on policy implications. It argues that it would be most productive for the long run if lending institutions were not bailed out. If the continuing existence of an institution was deemed essential, assistance should take the form of capital injections that dilute the equity of existing owners.